Pelatihan Pembuatan Nomor Ijin Berusaha untuk Kelegalitasan Usaha pada Pelaku Usaha di Kecamatan Pare Kabupaten Kediri - Umi Nadhiroh Umi; Diana Ambarwati; Srikalimah Srikalimah (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Pare District experienced an increase in the number of business actors. Many existing business actors do not know and understand the legality of business, namely the making of NIB. Meanwhile, the NIB itself plays an important role in the efforts of business actors. There are many advantages to having an NIB, one of which is the legality of the business.  The purpose of this community service activity is one way of socializing about the ease of making NIB permits by utilizing technology which will later make MSMEs advance to class. This service method is by providing training on how to make NIB online through the OSS application. MSME actors are guided by using simple equipment, namely through their respective cellphones by providing the required data in the form of ID cards and Business Certificates from their respective villages. The result of this assistance is that the actor can print the result in the form of an NIB certificate accompanied by a speaker. It is hoped that community service activities like this can provide solutions to the problems experienced by partners. By having a business license, MSMEs will have the potential for a wider marketing reach, business development and opportunities for cooperation and public trust in the product, obtaining legal protection in business in accordance with the location that has been determined; get empowerment opportunities both from the central, provincial and regional levels, can access financing to various bank and non-bank financial institutions.